Characterization of the ISO 9001:2015 standard through continuous improvement for its implementation in artificial intelligence organizations - Vázquez Cid de León, Carlos (2023)
ISO 9001:2015 is a standard for Quality Management Systems. Its implementation aims to improve the quality of the products or services provided by an organization to meet customer needs as well as legal and regulatory requirements. This standard uses the process approach, which includes the PDCA (Plan, Do, Check, Act) cycle and covers seven audit findings integrated into the system. To achieve the objective, a descriptive, cross-sectional, and non-experimental research was conducted. The results include a characterization of the ISO 9001:2015 standard, as well as a proposal that addresses the audit findings using different tools and methods, in order to comply with the requirements of the standard. At the end of the literature review, it was concluded that some articles only address a small part of the standard, which led to expand this research to generate a proposal that will be useful and serve as a methodological guide for organizations seeking certification in said standard and achieve continuous improvement.